PENINGKATAN LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN DENGAN LAYANAN INTI - Nasuka, Moh (DIKTUM: Jurnal Syariah dan Hukum, 2017)
Abstract: Customer loyalty has been recognized as an important source to maintain sustainable competition within an institution. One effort that can be done to improve customer loyalty is to provide customer satisfaction. Judging from the philosophical aspect, there is a very fundamental difference between the basic thinking of conventional marketing concepts with the concept of Islamic marketing. The concept of Islamic marketing based Maq?sid Syar?'ah Theory where the relationship of exchange or muamalah based on the values of worship to Allah SWT. The concept of Islamic marketing emphasizes on the aspect of maximization of value that is to obtain the benefit of life both in the world and the hereafter as the goal of Islamic Shari'ah decrease, not merely to pursue profit as much as possible. Such marketing concepts will shape the behavior of marketers to act in an honest and fair manner that grows from within the marketer's conscience, thus avoiding unethical behavior that can harm customers, themselves, or others.